Making online teaching accessible : inclusive course design for students with disabilities - Coombs, Norman, 1932- (San Francisco : Jossey-Bass, 2010)
'As educational institutions rapidly expand into online and hybrid formats, designing with accessibility in mind becomes essential. This book helps online teachers, instructional designers, and content developers avoid inadvertently creating barriers for students with disabilities and comply with government-mandated ADA standards. Grounded in the theories of learner-centered teaching and successful course design, the book explains how to design course content and delivery to be both attractive and accessible to all students, creating better conditions for student learning, success, and satisfaction, and better preparing students to compete in the competitive workplace.'--
Includes bibliographical references and index
Keywords: Students with disabilities -- Computer-assisted instruction; Computers and people with disabilities; Inclusive education